Genetic drift or natural selection? Hybridization and asymmetric mitochondrial introgression in two Caribbean lizards (Anolis pulchellus and Anolis krugi). (11th May 2013) - Jezkova, T.; Leal, M.; Rodríguez‐Robles, J. A.
Abstract: Hybridization and gene introgression can occur frequently between closely related taxa, but appear to be rare phenomena among members of the species‐rich West Indian radiation of Anolis lizards. We investigated the pattern and possible mechanism of introgression between two sister species from Puerto Rico, Anolis pulchellus and Anolis krugi, using mitochondrial (ND2) and nuclear (DNAH3, NKTR) DNA sequences. Our findings demonstrated extensive introgression of A. krugi mtDNA ( k ‐mtDNA) into the genome of A. pulchellus in western Puerto Rico, to the extent that k ‐mtDNA has mostly or completely replaced the native mtDNA of A. pulchellus on this part of the island. We proposed two not mutually exclusive scenarios to account for the interspecific matings between A. pulchellus and A. krugi . We inferred that hybridization events occurred independently in several populations, and determined that k ‐mtDNA haplotypes harboured in individuals of A. pulchellus can be assigned to four of the five major mtDNA clades of A. krugi . Further, the spatial distribution of k ‐mtDNA clades in the two species is largely congruent. Based on this evidence, we concluded that natural selection was the probable driving mechanism for the extensive k ‐mtDNA introgression into A. pulchellus . Our two nuclear data sets yielded different results. DNAH3 showed reciprocal monophyly of A. pulchellus and A. krugi, indicating no effect of hybridization on this marker. In contrast, the two species shared nine NKTR alleles, probably due to incomplete lineage sorting. Our study system will provide an excellent opportunity to experimentally assess the behavioural and ecological mechanisms that can lead to hybridization in closely related taxa.